2016
DOI: 10.1002/pd.4815
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of informational needs and received information following a prenatal diagnosis of congenital heart defect

Abstract: ObjectiveTo explore the need for information and what information was actually received following prenatal diagnosis of a congenital heart defect, in a country where termination of pregnancy beyond 22 weeks of gestation is not easily possible because of legal constraints.MethodsTwenty‐six Swedish‐speaking pregnant women (n = 14) and partners (n = 12) were consecutively recruited for semi‐structured telephone interviews following the prenatal diagnosis of a congenital heart defect. Data were analyzed using cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 32 publications
(70 reference statements)
5
70
1
1
Order By: Relevance
“…To deal with their difficult situation, they have a great need for information and support [15-18]. Preparatory information is an indicator of quality abortion care, and the literature suggests that women should always be offered sufficient information before the procedure [20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To deal with their difficult situation, they have a great need for information and support [15-18]. Preparatory information is an indicator of quality abortion care, and the literature suggests that women should always be offered sufficient information before the procedure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Preparatory information is an indicator of quality abortion care, and the literature suggests that women should always be offered sufficient information before the procedure [20]. However, people who undergo the procedure describe that they feel insufficiently informed about it, resulting in unanswered questions and unpreparedness [15-18]. To feel adequately prepared and well-informed, they search the Web for supplemental information about pregnancy terminations [17,18,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To feel adequately prepared and in control of their situation, patients seek out information before undergoing the procedure (Lafarge, Mitchell, & Fox, ). Indeed, studies have consistently shown that patients who undergo medical abortion in the second trimester of pregnancy have substantial needs for information before, during, and after the abortion process (Andersson, Christensson, & Gemzell‐Danielsson, ; Carlsson, Bergman, Karlsson, Wadensten, & Mattsson, ; Carlsson, Bergman, Wadensten, & Mattsson, ; Hunt, France, Ziebland, Field, & Wyke, ; Lafarge et al, ; Mukkavaara, Öhrling, & Lindberg, ). Health professionals who work with abortions regard preparatory information as an essential aspect of care (Gould, Perrucci, Barar, Sinkford, & Foster, ), and appropriate patient information is acknowledged in the literature as a decisive factor in order to achieve high‐quality abortion care (Dennis, Blanchard, & Bessenaar, ).…”
Section: Introductionmentioning
confidence: 99%